Acceptability of palliative care approaches for patients with severe and persistent mental illness: a survey of psychiatrists in Switzerland - Trachsel, Manuel (BMC Psychiatry, 2019)
BACKGROUND: Some patients develop severe and persistent mental illness (SPMI) which is therapy-refractory. The needs of these patients sometimes remain unmet by therapeutic interventions and they are at high risk of receiving care that is inconsistent with their life goals. Scholarly discourse has recently begun to address the suitability of palliative care approaches targeting at enhancing quality of life for these patients, but remains to be developed. METHOD: A cross-sectional survey asked 1311 German-speaking psychiatrists in Switzerland (the total number of German-speaking members of the Swiss Society for Psychiatry and Psychotherapy) about the care of SPMI patients in general, and about palliative care approaches in particular. 457 (34.9%) returned the completed survey. In addition, participants were asked to evaluate three case vignettes of patients with SPMI. RESULTS: The reduction of suffering and maintaining daily life functioning of the patient were rated as considerably more important in the treatment of SPMI than impeding suicide and curing the underlying illness. There was broad agreement that SPMI can be terminal (93.7%), and that curative approaches may sometimes be futile (e.g. 72.4% for the anorexia nervosa case vignette). Furthermore, more than 75% of the participating psychiatrists were in favour of palliative care approaches for SPMI. CONCLUSIONS: The results of the present study suggest that the participating psychiatrists in Switzerland regard certain forms of SPMI as posing high risk of death. Additionally, a majority of respondents consider palliative care approaches appropriate for this vulnerable group of patients. However, the generalizability of the results to all psychiatrists in Switzerland or other mental health professionals involved in the care of SPMI is limited. This limitation is important considering the reservations towards palliative care in the context of psychiatric illness, mainly because of the association with death and futility. Palliative care approaches, however, are applicable in conjunction with other therapies intended to prolong life. A next step could be to involve service users and develop a consensus of what palliative care might encompass in SPMI. A framework for identifying which patients might benefit from palliative care, should be explored for the future development of care for SPMI patients.